Ebola-Specific CD8+ and CD4+ T-Cell Responses in Sierra Leonean Ebola Virus Survivors With or Without Post-Ebola Sequelae. (21st May 2020) - LaVergne, Stephanie M; Sakabe, Saori; Kanneh, Lansana; Momoh, Mambu; Al-Hassan, Foday; Yilah, Mohamed; Goba, Augustine; Sandi, John Demby; Gbakie, Michael; Cubitt, Beatrice; Boisen, Matthew; Mayeux, Jessica M; et al.
Abstract: Background: Ebola virus (EBOV) disease has killed thousands of West and Central Africans over the past several decades. Many who survive the acute disease later experience post-Ebola syndrome, a constellation of symptoms whose causative pathogenesis is unclear. Methods: We investigated EBOV-specific CD8 + and CD4 + T-cell responses in 37 Sierra Leonean EBOV disease survivors with (n = 19) or without (n = 18) sequelae of arthralgia and ocular symptoms. Peripheral blood mononuclear cells were infected with recombinant vesicular stomatitis virus encoding EBOV antigens. We also studied the presence of EBOV-specific immunoglobulin G, antinuclear antibodies, anti–cyclic citrullinated peptide antibodies, rheumatoid factor, complement levels, and cytokine levels in these 2 groups. Results: Survivors with sequelae had a significantly higher EBOV-specific CD8 + and CD4 + T-cell response. No differences in EBOV-specific immunoglobulin G, antinuclear antibody, or anti–cyclic citrullinated peptide antibody levels were found. Survivors with sequelae showed significantly higher rheumatoid factor levels. Conclusion: EBOV-specific CD8 + and CD4 + T-cell responses were significantly higher in Ebola survivors with post-Ebola syndrome. These findings suggest that pathogenesis may occur as an immune-mediated disease via virus-specific T-cell immune response or that persistent antigen exposure leads to increased and sustained T-cell responses. Abstract : In this study, we evaluated Ebola-specific T-cell responses in Ebola virus disease survivors with or without post-Ebola syndrome, and we found that survivors with postinfectious sequelae had significantly higher CD8 + T-cell responses than survivors without sequelae.